Use and outcome of local anesthetic painkilling injections in athletes: A systematic review - Gultekin, S.; Chaker Jomaa, M.; Jenkin, R.; Orchard, J. W. (Clinical Journal of Sport Medicine, 2021)
Background: The use of local anesthetic painkilling injections to improve player availability is common practice in elite-level sport. Objective: To document the published use of local anesthetic injections in sport, according to number of injections, sites of injections, and complications reported. Data Sources: A systematic search of MEDLINE, Embase, CINAHL, AMED, Cochrane Database of Systematic reviews, SportDiscus, EBSCO Host, and Google Scholar. Results: One thousand nine hundred seventy local anesthetic injections reported on 540 athletes in 10 studies (from rugby league, American football, Australian football, and soccer) were reviewed. The most common areas of injection were as follows: the acromioclavicular (AC) joint; hand (including fingers); sternoclavicular joint (including sternum); rib injuries; and iliac crest contusions. Discussion: This review found some evidence of long-term safety for a limited number of injection sites (eg, AC joint) and some evidence of immediate complications and harmful long-term consequences for other sites. The quality of evidence is not high, with little long-term data and a lack of independent verification of the effects of the injections. Ideally, long-term follow-up should be conducted to determine whether these injections are safe, with follow-up undertaken independently of the treating physician and team. Conclusions: Based on limited publications, there is some evidence of long-term safety; however, there is a lack of clear proof of either absolute safety or long-term harm for many of these procedures. Physicians and players in professional sport should proceed with caution in using local anesthetic injections.